2022
DOI: 10.1021/acs.jafc.2c00881
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Process-Related Impurities and Corresponding Control Strategy in Biocatalytic Production of 2-O-α-d-Glucopyranosyl-l-ascorbic Acid Using Sucrose Phosphorylase

Abstract: 2-O-α-D-Glucopyranosyl-L-ascorbic acid (AA-2G) is an ideal substitute for L-ascorbic acid because of its remarkable stability and improved biological activity, which can be easily applied in cosmetic, food, and medicine fields. However, impurity identification and control are significant procedures during the manufacturing of AA-2G. This study assessed a manufacturing routine of AA-2G synthesized by sucrose phosphorylase (SPase). First, three unknown process-related impurities were observed, which were further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This could be due to the presence of different forms of ascorbic acid 33 or ascorbic acid impurities in the sample. 34 Different forms of ascorbic acid or ascorbic acid impurities would show different retention times. For example, dehydroascorbic acid, an oxidized form of ascorbic acid, can be detected by Miller’s method 35 along with the ascorbic acid detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to the presence of different forms of ascorbic acid 33 or ascorbic acid impurities in the sample. 34 Different forms of ascorbic acid or ascorbic acid impurities would show different retention times. For example, dehydroascorbic acid, an oxidized form of ascorbic acid, can be detected by Miller’s method 35 along with the ascorbic acid detection.…”
Section: Discussionmentioning
confidence: 99%
“…The total ascorbic acid content in the SDS was found to be the highest, but it was not detected in HPLC. This could be due to the presence of different forms of ascorbic acid or ascorbic acid impurities in the sample . Different forms of ascorbic acid or ascorbic acid impurities would show different retention times.…”
Section: Discussionmentioning
confidence: 99%
“…Triton X‐100 (0.5%) was used for liposomal demulsification. The AA2G and LAA content were determined according to the previous HPLC method, [ 39 ] and the standard curves were as shown in Figure S7 (Supporting Information). Zeroorder0.16emkinetics0.16emQtbadbreak=Q0goodbreak+k0normalt$$\begin{equation}{\mathrm{Zero - order}}\,{\mathrm{kinetics}}\,{{\mathrm{Q}}}_{\mathrm{t}} = {{\mathrm{Q}}}_{\mathrm{0}} + {{\mathrm{k}}}_{\mathrm{0}}{\mathrm{t}}\end{equation}$$ Firstbadbreak−order0.16emkinetics0.16emlogQtgoodbreak=logQ0goodbreak+k1normalt2.303$$\begin{equation}{\mathrm{First}} - {\mathrm{order}}\,{\mathrm{kinetics}}\,{\mathrm{logQ}}_{\mathrm{t}} = {\mathrm{logQ}}_{\mathrm{0}} + \frac{{{{\mathrm{k}}}_{\mathrm{1}}{\mathrm{t}}}}{{{\mathrm{2}}{\mathrm{.303}}}}\end{equation}$$ Higuchi0.16emModel0.16emQtbadbreak=kH0.33emt1/2$$\begin{equation}{\mathrm{Higuchi}}\,{\mathrm{Model}}\,{{\mathrm{Q}}}_{\mathrm{t}} = {{\mathrm{k}}}_{\mathrm{H}}\ {{\mathrm{t}}}^{{\mathrm{1/2}}}\end{equation}$$ Koresmeyerbadbreak−Peppas0.16emModel0.16emQtgoodbreak=kp0.33emtn$$\begin{equation}{\mathrm{Koresmeyer}} - {\mathrm{Peppas}}\,{\mathrm{Model}}\,{{\mathrm{Q}}}_{\mathrm{t}} = {{\mathrm{k}}}_{\mathrm{p}}\ {{\mathrm{t}}}^{\mathrm{n}}\end{equation}$$…”
Section: Methodsmentioning
confidence: 99%
“…HPLC showed that AA2G was hydrolyzed by 𝛼-glucosidase in the skin to produce L-ascorbic acid (LAA), with characteristic peaks at 5.047 and 6.313 min for LAA and AA2G, respectively (Figure S6, Supporting Information), respectively. [38,39] The release curves of A-CMH hydrogels showed an initial rapid release, followed by a gradual slowing down without any obvious abrupt release, as the release of AA2G needed to pass through two barriers: the lipid bilayer of liposomes and the hydrogel network. [5] Interestingly, the sustained release behavior of hydrogels on liposomes showed negative correlation with the DS of CMC, the higher DS resulting in weaker the sustained release effect.…”
Section: In Vitro Sustained Release Delivery Properties Of Liposome-h...mentioning
confidence: 99%
See 1 more Smart Citation